2011
DOI: 10.1080/14616734.2011.554005
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic correlates of attachment insecurity in a sample of women with eating disorders

Abstract: This study examined associations between attachment insecurity and autonomic response during the Adult Attachment Interview (AAI) in a sample of 47 women with eating disorders using a new system for the synchronous acquisition of behavioral and physiological data: the Bio Dual-channel and Representation of Attachment Multimedia System (BioDReAMS; Soares, Cunha, Zhan Jian Li, Pinho, & Neves, 1998). Consistent with the emerging literature on the psychophysiology of adult attachment, insecurity was positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…The secure adoptees showed a pattern of RSA withdrawal when confronted with an attachment-related stressor, which has been linked to more adequate responding to infant distress [50,51]. Our RSA outcomes are in line with the findings of Dias et al [17], who studied associations between attachment security and physiological reactivity during the AAI. They found some evidence for parasympathetic withdrawal in women with relatively secure AAI classifications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The secure adoptees showed a pattern of RSA withdrawal when confronted with an attachment-related stressor, which has been linked to more adequate responding to infant distress [50,51]. Our RSA outcomes are in line with the findings of Dias et al [17], who studied associations between attachment security and physiological reactivity during the AAI. They found some evidence for parasympathetic withdrawal in women with relatively secure AAI classifications.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that secure individuals show clearer signs of parasympathetic withdrawal or vagal tone (in combination with indices of mild sympathetic responses) when confronted with attachment-related stressors, which might be an indicator of more adequate responding to external stressors in these individuals compared to insecure individuals [37,51]. However, a replicable pattern of associations between quality of attachment and parasympathetic activity has not been established yet [17,32,48,55].…”
Section: Attachment and Emotional Reactivitymentioning
confidence: 93%
See 1 more Smart Citation
“…Effects of attachment characteristics on emotion-regulation are also observable on the level of autonomous functioning. Attachment insecurity is related to higher autonomous reactivity, while attachment security can offer better psychophysiological responses to interpersonal challenges in EDs (Dias et al, 2011). Furthermore, when attachment anxiety can be decreased through an ED treatment, outcomes may be better (Tasca et al, 2011; that supports the association between higher attachment security lower level of ED symptoms.…”
Section: Attachment and Eating Disorder Symptomologymentioning
confidence: 76%
“…The highest prevalence of eating disorders (ED) was found among the insecure-dismissing of attachment Salzman [18]. Young women with deactivating strategies were reported elevated levels of ED symptoms according to Cole-Detke and Kobak [19]. In another study on women with eating disorders it was found that one group were characterized by high control/restrictive features, while hyper-activating strategies were associated with the purging/binge eating.…”
Section: Introductionmentioning
confidence: 88%